Analysis of salmonella drug resistance in poultry sold in Jiading District from 2019 to 2020 - CHEN Peichao; HUANG Qiang; SUN Pan; DONG Yuting; PENG Qian (Shanghai yufang yixue, 2022)
ObjectiveTo investigate the contamination situation， serotype distribution and drug resistance of salmonella in poultry sold in Jiading District， Shanghai.MethodsBetween 2019 and 2020， four types of poultry meat （chicken， duck， goose and pigeon） were sampled from markets， and potential salmonella contamination was isolated and identified via serotyping. Furthermore， resistance detection of isolated salmonella to 13 commonly-used antibiotics was conducted.ResultsA total of 32 salmonella strains were isolated from 156 commercial poultry samples. No salmonella was identified in pigeon samples， while the most severe contamination was detected in goose samples， with a detection rate of 28.00%. Contamination situation was categorized with different storage conditions. The lowest detection rate of 12.90% was noted under cold storage， while the highest rate of 26.67% was detected under frozen condition. The major serotypes of salmonella were Salmonella typhimurium， Salmonella enteritidis and Salmonella Argonne. Relatively higher drug resistance was detected with nalidixic acid and tetracycline， with drug resistance rate of 59.38% and 40.63%， respectively. Low drug resistance was detected with cephalosporins， and no drug resistance was detected with imipenem. Significant difference in drug resistance was noted in the serotype of Salmonella isolated from meat of chicken， duck and goose. Three major salmonella strains had different drug resistance. 21.88% （7/32） of salmonella strains were non-resistant to any tested drugs. Multi-drug resistant strains accounted for 31.25% （10/32） of the isolated strains. At most， salmonella was resistant to 11 kinds of different antibiotics.ConclusionThere is a significant difference in the contamination situation and drug resistance of Salmonella isolated from four types of poultry meat sold in Jiading District， Shanghai. It is strongly recommended that different supervision strategies and management upon classification be implemented.